Copper-Catalyzed Oxidative Self-Coupling of α-Amino Carbonyl Compounds for the Synthesis of Tetrasubstituted 1,4-Enediones - Yi, Niannian; Xiong, Yi; Huang, Qingjun; Yan, Ning; Xie, Yanjun; Lan, Donghui; Yi, Ziqi; Au, Chak-Tong; Yi, Bing; Xiang, Jiannan (Synlett, 2018)
A protocol for the copper-catalyzed oxidative self-coupling of α-amino carbonyl compounds has been developed for the synthesis of tetrasubstituted 1,4-enediones (Z-isomers) in moderate to good yields through the cleavage of four sp3C–H bonds and the simultaneous formation of one C=C double bond in the α-amino carbonyl compound. The strategy has the advantages of using readily available starting materials and of high stereoselectivity.
Keywords: enediones; copper catalysis; oxidative coupling; amino carbonyl compounds; diaminobutenediones